Hubungan Indeks Massa Tubuh Dengan Perubahan Sudut Tibiofemoral Pada Lansia di Karang Werdha Dirgantara Malang - Valentina Avianti Utami; Agung Hadi Endaryanto; Dian Pitaloka Priasmoro; Ahmad Abdullah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: Elderly is a period of a person in which organ function has shown a decline. In addition, the elderly also experience a decrease in physical activity. An imbalance between physical activity and consumption can cause weight gain in the elderly. As body weight increases in the elderly, the body mass index also increases. High body mass index can cause deformity. The deformity of the knee joint can be a change in the angle of the tibiofemoral joint. The tibiofemoral joint is formed from the articulation between the convex surface of the femoral condyle and the condyle of the tibial plateau. The angle of the tibiofemoral joint in the frontal plane has a normal value of 5 degrees to 10 degrees valgum. Changes in the tibiofemoral angle can be caused by many factors such as a high body mass index which can lead to genu valgum deformity and genu varum deformity. Methods: This research method is analytical observation design with a cross sectional approach. The number of respondents in this study were 43 respondents consisting of 32 female respondents and 11 male respondents. The sampling technique used is random sampling. The statistical test used in this study is the Sommer's D test..Results: The results of statistical tests using the Sommer's D test obtained the value of P value 0.121, which means that the correlation between body mass index and changes in the tibiofemoral angle is very weak and the significant value is 0.391 (sig > 0.05).Conclusion: There is no correlation between Body Mass Index and Tibiofemoral Angle Changes in the Elderly Karang Werdha Dirgantara Malang